Energy usage in the manufacture of dairy powders: Advances in conventional processing and disruptive technologies. Issue 11 (18th March 2021) - Patil, Maheshchandra H.; Tanguy, Gaëlle; Floch-Fouéré, Cécile Le; Jeantet, Romain; Murphy, Eoin G.
Abstract: Spray drying is the gold standard for manufacturing dairy powders, due to its ability to maintain nutritional and functional properties and operate at high capacities. It is, however, extremely energy intensive, accounting for the largest share of total energy consumption in the powder manufacturing process. Therefore, spray dryer optimization, along with other water removal steps such as reverse osmosis and vacuum evaporation, is essential from a sustainability perspective. The objective of this paper is to review recent technological advances relating to product and process (reformulation, pretreatments and emerging technologies) which contribute to improved efficiency and reduced energy consumption in conventional spray drying based processes. Additionally, disruptive technologies that substantially reduce environmental footprint of powder manufacturing process by completely replacing spray drying are discussed.